PENERAPAN METODE DRILL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 001 JAPURA KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Dewi Apriani; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is based on the fact that happened in class V SD Negeri 001 Japura, who showed symptoms of low ability to absorb students in math. The problem of this research is